Tomographic imaging: multiple-fan-beam projection technique using optical fiber sensors - Abdul Rahim, Ruzairi; Leong, L. C.; Chan, K. S.; Pang, J. F.; Rahiman, M. H. Fazalul (SPIE-Int. Society Optical Enginering, 2007)
This paper presents the timing advantage of implementing a multiple-fan-beam projection technique using optical fiber sensors for a tomography system. To prepare the sensors to be used for this projection, a collimator is not needed, but optical fiber lens termination is crucial. In this research, the fiber optic lens for transmitters is modeled by experimental methods to transmit light at an emission angle of 30 deg. Due to this small emission angle, a multiprojection technique can be implemented without the light overlapping. A multiple-fan-beam projection technique is here defined as one allowing more than one emitter to project light at the same time using the switch-mode fan-beam method. This method can increase the optical sensor's ability for flow visualization. For the 32 pairs of sensors used, the two-projection technique and four-projection technique were investigated. Sixteen sets of projections formed one frame of light emission for the two-projection technique, and eight sets did so for the four-projection technique. Compared to the conventional single-light projection used in the switch-mode fan-beam method, multiple-light projection can achieve a higher data acquisition rate, thus minimizing data loss and producing a more accurate real-time tomographic image. For four projections the data acquisition rate is 609.76 frames/s.